Systematic literature review on the clinical and economic burden of human papillomavirus–related diseases in select areas in the Asia-Pacific region - Pei-Jen Lou; Wanatpreeya Phongsamart; Isaya Sukarom; Ying-Hui Wu; Omer Zaidi; Frieda Du; Alyssa Simon; Mark Bernauer (Human Vaccines & Immunotherapeutics)
Compared with Europe and America, adoption of human papillomavirus (HPV) vaccination into national immunization programs across the Asia-Pacific (AP) region has remained low. Moreover, HPV burden in this region has not been reviewed comprehensively. Therefore, this systematic literature review (SLR) aimed to summarize the clinical and economic burden of HPV and HPV-related diseases in select AP areas. An SLR was conducted January 2000-February 2022 using MEDLINE/Embase. Observational studies reporting incidence, prevalence, costs, or healthcare resource utilization (HCRU) of HPV and HPV-related disease among adults (≥18 years) from select AP areas were included. A total of 254 publications were included. Reported incidence per 100,000 person-years was 15.4–252.0 for cervical cancer (n = 5 publications), 0.2–55.5 for head and neck cancer (n = 7 publications), and 0.2–13.7 for anal cancer (n = 4 publications). Prevalence rates were 9.1%-100% for cervical cancer (n = 40 publications), 0.0%-95.6% for head and neck cancer (n = 48 publications), 0.0%-100% for anal cancer (n = 4 publications), 36.0%-79.6% for penile cancer (n = 4 publications), and 44.0%-82.0% for vaginal/vulvar cancer (n = 3 publications). Few studies reported on costs or HCRU, and high data variability was observed. Despite data variability, the high burden of HPV and HPV-related diseases makes clear the need for effective HPV screening, greater education, and reductions in vaccine hesitancy, particularly among lower- and middle-income areas. Improved data collection measures should be considered in data-scarce areas to better inform policy decision-making and improve monitoring of the impact of HPV vaccination.